Role of nurses in the assessment and management of chemotherapy-related side effects in cancer patients - Roe H (Dove Medical Press, 2014)
Helen Roe,1 Elaine Lennan2 1Department of Clinical Oncology, North Cumbria University Hospitals NHS Trust, Carlisle, 2Chemotherapy Unit, University Hospital Southampton NHS Foundation Trust, Southampton, UK Abstract: Chemotherapy services in the UK have been the subject of national policy directives for the past decade. These directives, amongst other things, include the development of nurse-led services; however, progress has been slow. This paper looks at the evidence for nurse-led services and discusses the competencies and skills required. Chemotherapy nurses have been much respected for their drug knowledge, information-giving, and communication skills, but in the past have lacked assessment skills. This paper offers a guide to assessment of chemotherapy patients, including the process of chemotherapy, key information needs, and consent, taking account of the recent 2013 National Cancer Patient Experience Survey. It discusses in detail the common side effects of treatment and their management, outlining international common toxicity criteria to guide assessment. Finally, it briefly outlines a new initiative of acute oncology services that have enhanced not only the quality of services but the safety of patients receiving chemotherapy. Keywords: chemotherapy, nurse-led care, acute oncology service, toxicity management